Eksploitasi Teknologi untuk Penipuan Digital: Studi Kasus Penyebaran Undangan Pernikahan Palsu di WhatsApp dan Implikasi Hukumnya di Indonesia - Ketut Ayu Asiti Sari; Made Sugi Hartono; Ni Ketut Sari Adnyani (Perspektif Administrasi Publik dan hukum, 2026)
Digital fraud, particularly schemes involving the distribution of fake wedding invitations through instant messaging applications such as WhatsApp, has developed into a serious problem in Indonesia along with the increasing use of digital technology in everyday life. This fraudulent modus operandi exploits victims’ curiosity, trust, and panic to prompt them to open malicious links or download harmful files containing malware. Such malware has the potential to damage device systems, steal personal data, and access sensitive information, including banking accounts and social media profiles. This form of fraud not only causes significant financial losses for victims but also results in psychological impacts, such as fear, trauma, and a loss of trust in digital communication. This article aims to comprehensively examine the modus operandi of digital fraud through fake wedding invitations, analyze the relevant legal framework, and assess the social and economic impacts on society. In addition, the article emphasizes the importance of improving digital literacy as an effective preventive measure to minimize the risk of digital fraud. To address this issue, the article proposes strengthening cooperation among law enforcement agencies, cybersecurity institutions, and technology service providers. Recommendations are also directed toward reinforcing regulations, enhancing the effectiveness of law enforcement, and intensifying public awareness campaigns to reduce the incidence of digital fraud in Indonesia.